A simulation of bubble growth on heating surface in subcooled boiling water based on the heat flows derived by experiment. (December 2019) - Cheng, Ning; Guo, Yun; Peng, Changhong
Highlights: Two single bubble growth processes have been recorded in a visual experiment. Bubble heat flows have been estimated according to experimental data. A numerical simulation has been conducted based on heat flow distributions. Abstract: Two growth processes of individual bubble on heating surface in subcooled boiling water were numerically studied based on the heat flows derived by experiment. In the experiment, a high speed camera was used to photograph the growth and condensation process of a single bubble in low subcooling degree water under normal pressure. The bulk fluid temperature and the temperature of heating wall at the nucleation point were recorded. Based on the experimental data of the bubble condensation process, the convective heat transfer formula at the bubble cap was derived and the heat flow distributions during the whole process were obtained. Then a numerical simulation of the whole process was conducted according to the heat flows. The bubble size, bubble shape and temperature fields were obtained. The simulation results can confirm the rationality and correctness of the theoretical analysis, for the bubble size is highly close to the experiment data. The results also indicated that the evaporation at the bubble base accounts for more than 45% of the total evaporation, which is mainly contributed by microlayer.